Passing training model based on small side game in futsal sports for senior high school students - Rizal, Agung Yudha Catur; Sugiyanto, Sugiyanto; Sabarini, Sri Santoso (Quality in Sport, 2020)
This research aims to : (1) Developing a futsal passing model based on small-sided games for high school futsal extracurricular participants. (2) Testing the feasibility of a small-sided games-based futsal passing training model for high school futsal extracurricular activities. 3) Test feasibility through small-scale and large-scale futsal passing training models based on small-sided games for high school futsal extracurricular participants. 4) Test the effectiveness level of the small-sided games-based futsal passing training model for high school futsal extracurricular activities between the experimental group and the control group. This research uses the development method (Research and Development) "proposed by Borg and Gall, The researcher adapted the research procedure into 3 main stages: stage 1 needs analysis, stage 2 product development and product trials, stage 3 product effectiveness tests. The sample was 30 extracurricular players. The research instruments were observation, interview, mixed questioner, the rating scale used was absolute rating scales, and field notes. Data analysis techniques are qualitative analysis and quantitative analysis. Qualitative data analysis was obtained from interviews and field notes. The quantitative analysis obtained from the prerequisite test was divided into two, namely the normality test and the homogeneity test using the SPSS vesi 18.0 software program. The effectiveness test uses t-test with SPSS version 18.0 software program. and comparative test. The research results are (1) Planning and implementation of futsal passing technique training during training is less varied, and the still low level of mastery of futsal passing technique during training. (2) The results of the feasibility test of experts obtained an average value of 81.11%. (3) The results of the group test using a small-sided games-based futsal passing training model on a small scale obtained an average value with a percentage of 81.4% and on a large scale obtained an average value with a percentage of 84.53%. (4) The results of the effectiveness test using the t-test in the experimental group obtained a significant value of 0.01. This means that a significant value of 0.01 <0.05 so that it can be concluded that there is a difference between the pre-test and post-test scores. The results of the effectiveness test using the t-test in the control group obtained a value of 0.925. This means that a significant value of 0.925> 0.05 so that it can be concluded that there is no difference between the pre-test and post-test scores.